URGENSI KEPALA SEKOLAH SEBAGAI PEMIMPIN PEMBELAJARAN DALAM MENCAPAI SEKOLAH BERPRESTASI PADA ERA DIGITAL - sulistyorini, Sulisytorini (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
This study aims to find out about the urgency of school principalleadership in achieving outstanding schools in the digital era. Thisstudy uses a qualitative approach, by seeking to explore the forms,factors, and implications of principal learning leadership in the digitalera. Data collection was conducted using participant observation atMTsN 2 Blitar and interviews with the principal and five teachers atthe school. The results of this study indicate that, first, the principal'slearning leadership in the digital era is by creating a school environmentthat is responsive to digitalization, providing LEDs in each class andallowing students to bring smartphone to school according to the needsand material presented by the teacher. Second, there are challengingfactors that come from within and from outside the institution,including human resources that do not respond to digital learning andexternal obstacles, the lack of funds from the Ministry of Religion fordigitalization-based learning, and the lack of supporting infrastructurefor digital learning in madrasas. The three implications of the schoolprincipal's learning leadership are the creation of a conducive digital-based learning environment climate so that institutional and studentachievements, both academic and non-academic, are achieved so thatthey become national-level pilot madrasah.